Oral rehabilitation in ectodermal dysplasia - Khan, MH; Mishu, MP; Haque, S; Mohsin, F (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):627-31 The abstract of this article is available on the PubMed website